Nano particle formulation of Phoenix dactylifera L. (ajwah and black date) seed and peel and investigating their antioxidant and antibacterial properties - badawi, jailan essam (AUC Knowledge Fountain, 2019)
Bacterial infection is one of the leading causes of death world-wide. Antibiotics have always been the first choice to be used against bacterial infections especially in post-surgery, diabetes mellitus due to their lack of immunity and in organ transplantation as well. On the other side the medical antibiotics have a major problem which is the resistance; meaning that after sometime the body begins to resist them and they became with no action on bacteria. That is why it is a global trend now to shift back to the natural resources from plant origin which exhibit potent antibacterial action. As an example is the date pit Phoenix dactylifera L. (Ajwah and Black date) which was proven to have many medical uses; antimicrobial, antifungal, anti-diabetes mellitus type 2, reduces obesity and hypercholesterolemia, protection against coronary heart diseases. This study is focused on using Black and Ajwah date pit and fruit, black date fruit to form nano formulation that are expected to have unique antioxidant and antibacterial activities. To the best of our knowledge No previous work was done to formulate a nano particle out of the pit. Date pit extract was prepared as aqueous and/or alcoholic. The chitosan nanoparticle was formulated to encapsulate the date pit extract inside it by the help of the sodium tri-poly phosphate (TPP) linker to enhance coiling and encapsulation by applying certain stirring criteria including the time, speed and temperature of stirring, centrifugation and sonication. Those separated nanoparticles will be measured to guarantee their size and potential. Spectroscopic and physicochemical assessments were done using X-ray diffractometer (XRD) and Transmittance Electron microscopy (TEM) to guarantee their homogenous spherical shape and size. Then measurements were done by Ultraviolet-Visible spectrophotometry (UV-Vis), Infra-red spectrophotometry (IR). They proved that AS OD NPs were of hydrodymanic size 152.3-254.93 ±60 nm and TEM size of 1.01-2.05 nm, poly dispersion index of 0.39±0.08 and potential of 32.49-35.21±0.4. the NPs encapsulation AS extract in ratio of chitosan : ASOD 1:7 (w/w) had encapsulation efficiency of 70.37% and loading capacity of 61%. Release rate of those NPs was 68.2%±0.04 at 48 hrs. They showed enhanced antioxidant and antibacterial actions where the NPS were 1.2 fold more antioxidant than the plant extract and 100 fold more antibacterial than the plant extract